2020
DOI: 10.1038/s41598-020-73202-0
|View full text |Cite
|
Sign up to set email alerts
|

Renal fibrosis detected by diffusion-weighted magnetic resonance imaging remains unchanged despite treatment in subjects with renovascular disease

Abstract: Tissue fibrosis is an important index of renal disease progression. Diffusion-weighted magnetic resonance imaging’s (DWI-MRI) apparent diffusion coefficient (ADC) reveals water diffusion is unobstructed by microstructural alterations like fibrosis. We hypothesized that ADC may indicate renal injury and response to therapy in patients with renovascular disease (RVD). RVD patients were treated with medical therapy (MT) and percutaneous transluminal renal angioplasty (MT + PTRA) (n = 11, 3 bilaterally, n = 14 kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…CKD of most origins is marked by fibrosis in addition to reduced glomerular filtration, which contributes to a decrease in the tubular volume fraction (46). In addition to pathological changes in the tubular volume, our simulations revealed that NNLS continuum modelling for renal DWI may also be useful for detection and treatment monitoring of renal fibrosis, which is an important biomarker of CKD and a powerful predictor of renal outcome (26,28). These same considerations likely apply to pathologies such as kidney lesions, polycystic kidney disease, or tumors.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…CKD of most origins is marked by fibrosis in addition to reduced glomerular filtration, which contributes to a decrease in the tubular volume fraction (46). In addition to pathological changes in the tubular volume, our simulations revealed that NNLS continuum modelling for renal DWI may also be useful for detection and treatment monitoring of renal fibrosis, which is an important biomarker of CKD and a powerful predictor of renal outcome (26,28). These same considerations likely apply to pathologies such as kidney lesions, polycystic kidney disease, or tumors.…”
Section: Discussionmentioning
confidence: 84%
“…Tubular atrophy and interstitial fibrosis play a major role in the microstructural changes occurring during kidney pathology e.g., renal allograft injury (24). Being able to assess renal fibrosis and alterations in the tubular volume fraction with non-invasive MRI would be clinically valuable (3,7,22,23,(25)(26)(27)(28). Second, as the renal capsule is comparatively rigid, changes in the tubular volume fraction will result in opposite changes in the renal blood volume fraction, thereby confounding the relationship between renal blood oxygenation leveldependent (BOLD) T 2 *, oxygen saturation of hemoglobin, and tissue partial pressure of oxygen (21,29).…”
Section: Introductionmentioning
confidence: 99%
“…Renal ADC has been shown to correlate with interstitial fibrosis in several studies [147][148][149], although less is known about the exact underlying processes affecting the DWI signal [150]. The correlation between ADC and established biochemical biomarkers of kidney function and damage (i.e., GFR and UACR) in DKD patients has been confirmed in the univariate analysis of Makvandi et al [48].…”
Section: Dwimentioning
confidence: 91%
“…By adding mGFR as one variable, however, ADC was no longer significant in the bivariate prediction of UACR, suggesting that ADC could be linked to UACR via its effect on GFR. Interestingly, the ADC remained unchanged during 3 months of therapy in patients with renovascular disease and mild fibrosis and did not correlate with eGFR, serum creatinine, renal hypoxia, or inflammation, which could suggest that these factors are not captured in the ADC values [147]. In a sub-study of the COMBINE trial, baseline cortical ADC significantly correlated with the annual, patient-specific eGFR slope over 12 months (p = 0.08), although this was no longer significant once albuminuria was adjusted for, suggesting that there is either overlapping information between ADC and traditional risk factors for CKD progression, or albuminuria is a causal pathway to CKD progression [151].…”
Section: Dwimentioning
confidence: 97%
“…Diffusion-weighted imaging (DWI)-MRI is capable of estimating ischemia/reperfusion injury delaying graft function, 54 but it cannot predict renal artery revascularization success. 55 Very recent developments include hyperpolarized-[1- 13 C]pyruvate imaging, allowing evaluation of metabolic status directly in ischemic kidneys 56 and MRI-CEST (chemical-exchange-saturation-transfer) pH-mapping to evaluate both acid-base homeostasis and renal filtration. 57 Viability.…”
Section: Oxygenationmentioning
confidence: 99%